Rancang Bangun Aplikasi Digital Library Berbasis Web Menggunakan Framework Laravel Pada Desa Tugu Utara - Putra, Rakha Dimas; Feta, Neneng Rachmalia (Teknik Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Buana Perjuangan Karawang, 2024)
This study develops a web-based digital library application in Desa Tugu Utara using the Laravel framework. The main problem is the inability of the Desa Tugu utara library system to efficiently and modernly manage and provide information. This application provides features such as digital books, online book borrowing and returning, book searching and filtering, interactive education in the form of quizzes, and library management that facilitates admin tasks. The development follows the waterfall method, including Requirements Definition, System and Software Design, Implementation, and Integration and System Testing. Requirements Definition analysis identified 22 main functional requirements. System design uses UML diagrams, such as Use Case Diagrams, Activity Diagrams, Class Diagrams, and Entity-Relationship Diagrams (ERD). The UI/UX design was created with Figma for easy layout and navigation. System testing with blackbox, integration testing, and validation testing ensures all components function well and meet user needs. System Usability Scale (SUS) testing shows excellent usability with an average score of 85.20. Overall, this application achieves the research objectives and shows significant potential in digital library management in Desa Tugu Utara.